(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers chose this study to focus on women who experienced violence at Barangay 176 Bagong Silang Caloocan City. It is devastating to know that one out of three women globally experiences violence based on the World Health Organization (WHO). R.A No. 9269 is an act defining violence against women and their children, providing protective measures for victims, prescribing penalties, and for other purposes. All women must know our rights and the law that protects us. In this study, we want to assess the impact of violence on their daily lives and know the factors or common violence they experience. This will help us come up with accurate conclusions and good recommendations to help the victims and the Barangay they are in. The researchers used a descriptive design with a situational approach to assess the impact of violence on the victim’s daily lives. The researchers interviewed some women who were victims of violence and the Barangay officials who assessed the victims. The study concluded that most respondents were between 26 and 33 years old and at the college level. Third-party harassment, name-calling, abusive anger, and downgrading happened very often, according to respondents. Measures proposed to the Barangay in response to the victims’ complaints were interpreted as "highly recommended." The study’s findings show the implementation, scope, and limitations of the impact of violence against women on their daily lives. This information can be used by the Barangay officials at Barangay 176 Bagong Silang Caloocan City to implement better recommendations to help the victims in useful ways and for their Barangay to be better at serving them.